IMPROVING CPR PERFORMANCE IN NURSES USING METRONOME GUIDANCE: A REVIEW ARTICLE (The Research of Medical Science Review, 2025)
Background: Cardiopulmonary resuscitation (CPR) is a critical, life-saving procedure requiring precise execution of chest compressions and ventilations to maintain circulatory and respiratory function during cardiac arrest. The quality of chest compressions particularly their rate, depth, and rhythm has a direct impact on patient survival outcomes. Metronome-guided auditory feedback has been proposed as an intervention to enhance CPR performance.Objective: This review critically evaluates and synthesizes existing literature on the effectiveness of metronome-guided interventions during CPR performed by nurses, with emphasis on their influence on key CPR performance metrics such as compression rate, depth, and rhythm consistency.Method and Materials: A comprehensive literature search was conducted across multiple databases including CINAHL, PubMed, and ScienceDirect. Keywords employed were: cardiac arrest, cardiopulmonary resuscitation, metronome-guided CPR, CPR performance metrics, chest compression quality, nurses, auditory feedback, and CPR training. Boolean operators (AND, OR, NOT) and a publication date filter from 2020 to 2024 were applied. Result: Evidence from reviewed studies demonstrates that the use of metronome guidance significantly improves chest compression fraction and overall CPR quality metrics. This enhancement correlates with increased potential for improved patient survival during cardiac arrest.Conclusion: Metronome-guided auditory feedback is an effective tool to improve CPR performance among nurses. Incorporating metronome guidance into CPR training and clinical practice may enhance the quality of resuscitation efforts and potentially improve patient outcomes.